2011
DOI: 10.1017/s1368980011001108
|View full text |Cite
|
Sign up to set email alerts
|

What's in the lunchbox? Dietary behaviour of learners from disadvantaged schools in the Western Cape, South Africa

Abstract: Objective: To identify and describe factors associated with food shop (known as tuck shop in South Africa) and lunchbox behaviours of primary-school learners in South Africa. Design: Analysis of data collected in 2008 from a cross-sectional survey. Setting: Sixteen primary schools in the Western Cape, South Africa. Subjects: A total of 717 grade 4 learners aged 10-12 years. Results: A 24 h recall established that 69 % of learners carried a lunchbox to school and 49 % had consumed at least one item purchased fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 18 publications
3
49
1
Order By: Relevance
“…The number of children carrying a lunch box was low and, similar to the results of a previous localised study (24) , the contents consisted mostly of bread. Previous studies have shown that learners who attended schools of high socio-economic status were twice as likely to bring food to school (13) and that learners from rural and disadvantaged settings were less likely to bring a lunch box to school because of a lack of food available at home (24) .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The number of children carrying a lunch box was low and, similar to the results of a previous localised study (24) , the contents consisted mostly of bread. Previous studies have shown that learners who attended schools of high socio-economic status were twice as likely to bring food to school (13) and that learners from rural and disadvantaged settings were less likely to bring a lunch box to school because of a lack of food available at home (24) .…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that learners who attended schools of high socio-economic status were twice as likely to bring food to school (13) and that learners from rural and disadvantaged settings were less likely to bring a lunch box to school because of a lack of food available at home (24) .…”
Section: Discussionmentioning
confidence: 99%
“…Since the pilot took place in the HK study schools the year before the implementation commenced, the pilot sample did not include any children from the final HK sample. As described in an earlier publication, 27 a multiple correspondence analysis was carried out on all questions contributing to the nutritional knowledge and nutritional self-efficacy constructs during the analysis of this pilot data. The Burt matrix approach 28 was applied and the percentage of variability in the first two dimensions of each score was assessed.…”
Section: Knowledge Self-efficacy and Behavior Questionnairementioning
confidence: 99%
“…Other smaller regional studies in younger age groups support this observation to varying degrees. 43,44,46 Many children were now receiving fruit and vegetables through the National Schools Nutrition Program (NSNP). 42 This was made possible by an increase in the average meal cost allowance per student per day since the last report card and the addition of a guideline to allow for fresh vegetables or fruit to be served daily.…”
Section: Nutritional Indicatorsmentioning
confidence: 99%